Infrastructure Requirements for Cybersecurity - Durmus, Omer; Varol, Asaf; Varol, Nurhayat (Institute of Electrical and Electronics Engineers Inc., 2019)
The aim of this study is to create a model to meet the global infrastructure requirements of cybersecurity. The general framework of the study was determined by examining the cybersecurity infrastructures used around the world and the improvements needed by these infrastructures, and by synthesising the research on how to provide an effective solution with an innovative model. © 2019 IEEE.
1st International Informatics and Software Engineering Conference, IISEC 2019 -- 6 November 2019 through 7 November 2019 -- Ankara -- 157111
Keywords: Cybersecurity; cybersecurity infrastructure; vulnerabilities